2008
DOI: 10.1063/1.2977674
|View full text |Cite
|
Sign up to set email alerts
|

The roles of the various plasma agents in the inactivation of bacteria

Abstract: The roles of various plasma agents in the inactivation of bacteria have recently been investigated. However, up to now, the effect of the charged particles on the inactivation of bacteria is not well understood. In this paper, an atmospheric pressure plasma jet device, which generates a cold plasma plume carrying a peak current of 300 mA, is used to investigate the role of the charged particles in the inactivation process. It is found that the charged particles play a minor role in the inactivation process whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
137
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(155 citation statements)
references
References 34 publications
9
137
0
4
Order By: Relevance
“…Therefore, the UV radiation served a minor role in the sterilization of the bacteria (19,32). Heat was not responsible for the bactericidal effect, since the plasma jet with or without the working gas flowing through 3% hydrogen peroxide was at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the UV radiation served a minor role in the sterilization of the bacteria (19,32). Heat was not responsible for the bactericidal effect, since the plasma jet with or without the working gas flowing through 3% hydrogen peroxide was at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the size of inhibition zone by transporting plasma was always larger than TP cross section. As shown by Lu, 2008 andGoree, 2006, oxygen-reactive species generated by the plasma jet such as O, and O 3 , can diffuse radially outward and consequently deactivate cells [2,56]. On the other hand, UV photons produced in atmospheric plasma jets propagate preferentially along the plasma column thus they interact only with a part of the target surface located just under the jet [57].…”
Section: Inactivation By Single Transporting Plasmamentioning
confidence: 99%
“…Atmospheric-pressure room-temperature plasma jets have attracted a lot of attention for numerous applications in plasma medicine [1][2][3][4][5], surface and materials processing [6][7][8][9]. Although the discharges in plasma jets typically appear as continuous plasma, high-speed imaging shows that the plasma in fact comprises discrete, fast moving plasma bullets [10][11][12], or ionization waves (IWs).…”
Section: Introductionmentioning
confidence: 99%
“…For sterilization, there are reports on the inactivation of bacteria, such as Escherichia coli [5,6], Micrococcus luteus [7], and Staphylococcus aureus [8], using atmospheric-pressure plasma and on the disruption of Bacillus subtilus spores [9,10] and Bacillus atrophaeus spores [11,12]. For medical applications, it was reported that the irradiation of mammalian cells with atmospheric-pressure plasma caused their necrosis [13] or apoptosis [14] depending on the irradiation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows a schematic of the experimental setup used in this study. In the unit to generate a plasma jet, a copper tube (inner diameter, 4 mm; outer diameter 6 mm) as the discharge electrode was inserted into a dielectric quartz tube (length, 50 mm; inner diameter, 6 mm; outer diameter, 8 (thickness, 0.05 mm; width, 10 mm) was wrapped as the ground electrode [29]. A high AC voltage was applied to induce dielectric barrier discharge inside the quartz tube between the electrodes and to convert the introduced Ar gas to plasma, which was ejected into air in the form of a jet.…”
Section: Introductionmentioning
confidence: 99%